Efficacy and safety of oral Chinese patent medicine for benign prostatic hyperplasia: a network meta-analysis of randomized controlled trials - Tang, Yiwen; Cai, Yuyang; Ding, Jiasen; Ji, Ronfu; Wang, Xiong; Zhang, Zejia; Xu, Feng; Gao, Zhan (Frontiers in Medicine, 2024)
Objective This paper aims to evaluate the disparities in efficacy and safety across various oral Chinese patent medicines for the treatment of benign prostatic hyperplasia (BPH), using a frequency-based reticulated meta-analysis. Methods The researchers searched the following databases: Web of Science, PubMed, Excerpta Medical Database (Embase), Cochrane Library, China Knowledge Network (CNKI), China Biomedical Literature Service System (SinoMed), Wanfang Data Knowledge Service Platform and China Science and Technology Periodicals Database (VIP). Besides, the researchers collected all randomized controlled trials (RCTs) of oral Chinese patent medicines, as well as simple preparations and simple preparations for benign prostatic hyperplasia from the establishment of the database until July1, 2024. After two researchers independently screened literature, extracted data, and evaluated the risk of bias in the included studies, a net meta-analysis was conducted using Stata 16.0 software. Results Seventy-two RCTs involving 15 oral Chinese patent medicines and a total of 7,800 patients were included. Net meta-analysis manifested that “Jinkuishenqi capsule (JKSQ) + conventional western medicine (CWM)” was the most effective way in increasing total efficiency ratio. “Huange capsule (HE) + CWM” was the most effective method in decreasing prostate volume. “Qianliesutong capsule (QLST) + CWM” was the most effective approach in decreasing residure volume. “Xialiqi capsule (XLQ) + CWM” was the most effective way in increasing maximum urinary flow rate. “Longbisu capsule (LBS) + CWM” was the most effective method in decreasing international prostate symptom score (IPSS). To reduce the adverse reactions, “HE + CWM” has the best efficacy. Considering both drug efficacy and safety, “Ningmitai capsule (NMT) + CWM” would be the most ideal choice. Conclusion Based on NMA, JKSQ, HE, QLST, XLQ, LBS, NMT plus CWM have been proved to possess the highest probability of being the best therapy. Due to the limitations of this study, these results should be confirmed through detailed randomized controlled trials. Systematic review registration https://www.crd.york.ac.uk/prospero/, Identifier, CRD42023484071.